PREVALENSI ANEMIA PADA ANAK 2-4 TAHUN DI DKI JAKARTA SERTA FAKTOR RISIKONYA - Sumarno, Iman; Kartika, Vita; Saraswati, Edwi (GIZI INDONESIA, 2005)
Anemia in young children causes retardation in growth and development, and low immunity. The crisis that hit Indonesia, decreased socio- economic status of the populations and public services. Hellen Keller International reported high prevalance of anemia in young children in poor areas of Indonesia. Aware about the severe consequences of anemia, Provincial Health Office of Jakarta in 2002 assesed the magnitude of anemia in children aged 2-4 year in Jakarta. The survey was planned to represent each areas of Jakarta, namely West Jakarta, Central Jakarta, East Jakarta, South Jakarta, North Jakarta, and district of Pulau Seribu. Thirty clusters were systematically drawn in each cluster 7 children aged 2-4 years were systematically random in each cluster. It was found that the education level of parents were relatively low: among mother of the samples 85% were house wivesand 38% of the father were in informal sectors. The prevalance of anemia of children aged 2-4 years was 26,8%. It ranges from 13.5 % in South Jakarta to the highest 51.3 % in Pulau Seribu. The risk factors of anemia for children were underweight and ever defecate worm with increased risk 1.5 and 1.9 ti. On the other named comsumption of vitamin A capsules more then 3 times. is protective agains anemia as low as 27%. Having parents or working in company reduced risk of anemia by 33%.Keywords:anemia, risk factors